Towards a Methodology for Semantics Specification of Domain-specific Models through Properties - Van Der Straeten, Ragnhild (Electronic Communications of the EASST, 2011)
Domain-specific languages are designed for a specific domain and their use in the development of a software system enables domain experts to understand and develop models. The full description of a complex software system uses various domain-specific languages, each language having its own meaning. The definition of the precise semantics of domain-specific models is an important problem because semantics are a necessity to develop tools allowing formal analysis and verification. Current approaches focus on specific formalisms or languages which are the most appropriate to reason about certain properties. In this work we propose an approach that allows domain experts to specify the semantics of domain-specific models through properties expressed in a domain-specific language. The advantage of the approach is that domain experts can write down and understand the properties of the models.